A communicating object's approach for smart logistics and safety issues in warehouses. (March 2017) - Trab, Sourour; Bajic, Eddy; Zouinkhi, Ahmed; Thomas, André; Abdelkrim, Mohamed Naceur; Chekir, Hassen; Ltaief, Radhouane Hadj
A communicating object, or connected object, is a key element of the Internet of Things to shift a perceptible real world into a wide digital virtual world known as the cyber-physical system. Knowing that sustainability, safety, and logistic issues are among the significant goals and challenges of modern industrial enterprises, the communicating object can be a relevant concept to guarantee safety performance in logistics and warehouse management. This article presents the impacts and advantages of the communicating object in smart logistics and the design of a communicating object model inspired from Internet of Things European research projects, which controls and monitors safety risks in a hazardous and chemical industrial context. Generic safety-based scenarios are presented, which rely on a set of negotiated interaction mechanisms for storage and picking. The relevant deployment of intelligence in a warehouse management system leads to propose a new concept called "IoT-controlled Safe Area." Our contribution is to bring informational, communicational, and decisional capabilities close to the warehousing physical world thanks to the communicating object. This enables achieving safety assurance with a decrease in the decision-making delay and an increase in the solving efficiency of local and dynamic disruptions, while avoiding inherent shortcomings of the warehouse management system centralization. For this, an industrial implementation is presented.